Clinical features of Primary Open Angle Glaucoma at initial presentation: Experience at a tertiary eye care center in Nigeria - Okosa, Michael Chuka; Apakama, Akunne Ijeoma; Onwuegbuna, Arinze Anthony; Uzozie, Chukwudi Charles; Amobi, Miriam-Benigna Chika; Onyekwe, Lawrence Obizoba; Uzuke, Chinwe (Journal of Ophthalmology and Research, 2021)
Introduction: Glaucoma is a group of optic neuropathies and the leading cause of irreversible blindness worldwide. Primary open angle glaucoma is the commonest type of glaucoma. In affected people, optic nerve fibres are damaged with ensuing loss and raised intraocular pressure in some sufferers. Aim/objectives: To increase knowledge and understanding for improved care of primary open angle glaucoma patients. Method: This was a retrospective study of consecutive 167 hospital patients presenting in Guinness Eye Center Onitsha over a period of February to December 2018 who were diagnosed as having primary open angle glaucoma. Relevant clinical data were studied. Descriptive and correlation statistics were used to ascertain significance of features detected. Results: The patients were 87 (52.1%) males and 80 (47.9%) females. The age range was 17 to 76 years (Mean of 56.4 ± 3.02 years). Mean duration of disease before presentation was 30.4 ± 5.9 months. Visual acuity at presentation was less than 3/60 in 121 (36.2%) eyes. Intra-ocular pressure mean was 26.6 ± 1.6mmHg. The mean of Cup to optic disc ratio is 0.77 ± 0.2. The visual field loss was total or advanced in 69.6%. Using Pearson’s correlation 2-tailed test: cup/disc ratio correlates with duration of presenting symptoms in months at p=0.05, and with intra-ocular pressure at P= 0.01 On non-parametric correlation, using Spearman’s rho 2-tailed test, at p= 0.5, duration of presenting symptoms correlates with age; and at P = 0.01 cup/disc ratio correlates with level of intraocular pressure Conclusion: Primary open angle glaucoma present at an advanced stage of the disease. Advocacy is needed for dissemination of information about this disease and where to get care.